Nazir Wakaf Profesional, Standarisasi dan Problematikanya - Baharuddin, A Zamakhsyari; Iman, Rifqi Qowiyul (Institut Agama Islam Negeri Kendari, 2018)
Among the obstacles of waqf law implementation is the problem of nazir which is stilltraditional-consumptive due to the lack of understanding of waqf and the low quality ofhuman resources. This paper will discuss the problems of nazir which include, definitions, obligation, criteria of professional nazir, obstacle and solutions. Based on the results of study, it is concluded that the requirements of professional nazir contains moral, management and business as well as other supporting knowledge and insights. In addition, professional nazir should master human skill, technical skills and human relations. While the obstacle consists of lack of knowledge, coaching, recruitment, reward, competence and supervision. And among the solutions that can be done are changes of paradigm, the existence of Nazir associations, the establishment of Nazir schools, and increasing the welfare of Nazir